PENINGKATAN KETERAMPILAN SISWA DALAM PEMANFAATAN LIMBAH SABUT KELAPA DI PKBM SINAR MULIA - Agus Pariono; Andi Yusuf Katili; Waldi Patadjenu; Sofyan Alhadar (Jurnal Pengabdian kepada Masyarakat (J-PMas), 2024)
Coconut fiber is one of the components of coconut fruit which, when processed and decomposed, can become a product needed for the domestic market and even become a product with high export value. Coconut fiber (cocofiber) and coconut fiber powder (cocopeat) are two products derived from coconut fiber which have benefits and can be used as industrial and agricultural products. PKBM Sinar Mulia is a center for community learning activities. In Puncak Village, you can find many coconut trees which are processed into coconut milk, cooking oil and also made into copra or sold to factories. However, the current problem is that people only take the meat to make copra and send it to the factory without paying attention to the benefits of coconut fiber. For this reason, it is necessary to carry out outreach and provide training on coconut fiber waste skills so that it has economic value, which of course has a very positive impact on the people who live around coconut tree plantation locations. If this coconut fiber can be processed properly with assistance and provision of skills materials in processing this waste.